Just Another level? Comparing Quantitative Patterns of Global School and Higher Education Expansion - Bilal Barakat; Robin Shields (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2016)
The expansion of enrolment and attainment is a key theme in higher education research. In particular, research has examined cross-national determinants of higher education expansion while understanding expansion through the relationship between higher education and the labour market. Early work on higher education expansion established a key framework for classifying enrolment levels, but empirical studies on the global expansion of higher education are scarce. This study addresses this gap by comparing the existing patterns of higher education expansion to those experienced at other levels on the course to universal or nearuniversal access. We demonstrate that a model fitting universal access trajectories fits higher education as well as other levels of education, and, therefore, there is no prima facie reason to believe that its expansion will face ceilings or saturation levels based upon available evidence. Claims that are premised on such a ceiling should therefore consider empirical evidence for this assumption in their analysis. These findings contribute to discussions on higher education expansion as well as studies of higher education and the labour market.
Keywords: 300; higher education; post-secondary education; expansion; attainment; universalisation; labour market